Nutritional composition of meals at work and its relationship with manufacturing workers’ anthropometric profile and energy expenditure (2016)
The objective of this study was to verify whether the energy content and nutritional composition of meals consumed at work (lunch) correlated with the energy expenditure and nutritional status of workers from different sectors (administration and production) of different industries. The sample consisted of 292 workers. Many anthropometric dimensions were assessed, such as physical activity energy expenditure, and daily energy expenditure (DEE). Food intake was measured directly for five days. The study comprised an assessment of the correlation between sectors and gender, a qualitative assessment between obesity indicators, and a principal component analysis (PCA). Overweight workers prevailed, and DEE differed by gender and work sector (p0.05). PCA showed that the majority of the individuals with high energy expenditure and high energy and fats consumption levels were males.